Implementation of STEM-Integrated PjBL Based on Lesson Study: Improving Students' Critical Thinking Skills - Nurdiana, Lizza; Winaryati, Eny; Maharani, Endang Tri Wahyuni; Ikhsan, Zanaton H; Rauf, Rose Amnah Abd; Salaffudin, Affan (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to examine the application of lesson study design on chemistry material in improving critical thinking skills of students in class XI-2 SMA Negeri 2 Semarang. The research was conducted for three meetings involving the implementation of Project-Based Learning (PjBL) learning model with STEM (Science, Technology, Engineering, Mathematics) approach. The lesson study stages included planning, implementation, and reflection focusing on reaction rate material, involving students in collaborative activities such as designing and testing simple tools. The results showed that the application of the STEM-based PjBL model significantly improved students' critical thinking skills. This improvement can be seen from students' ability to identify, analyse, and solve problems based on relevant theories. The learning activities implemented, such as group discussions and windows shopping activities, also play an important role in improving interaction and collaboration between students. The implementation of STEM in PjBL not only deepens students‘ understanding of chemical concepts, but also increases students’ interest and active participation in the learning process. This study concludes that the application of STEM-based PjBL learning model, collaborated with lesson study, is able to improve critical thinking skills and the quality of chemistry learning on reaction rate material.